Pelatihan Pengelolaan dan Pemilahan Sampah Pada BUMDes Banjarwaru Sejahtera Untuk Menunjang Kemandirian Masyarakat Desa Banjarwaru - Wanti, Linda Perdana; Ariawan, Radhi; Prasetya, Nur Wachid Adi (Universitas Negeri Gorontalo, 2024)
The Community Service (PKM) activity carried out in Banjarwaru Village aims to empower the community through structured and effective waste management. The partner in this program, namely BUMDes